Prospective surveillance study of haemophilia A patients switching from moroctocog alfa or other factor VIII products to moroctocog alfa albumin-free cell culture (AF-CC) in usual care settings - Lopez, Rafael Parra; Nemes, Laszlo; Jimenez-Yuste, Victor; Rusen, Luminita; Cid, Ana R.; Charnigo, Robert J.; Baumann, James A.; Smith, Lynne; Korth-Bradley, Joan M.; Rendo, Pablo (Thrombosis and Haemostasis, 2015)
This prospective, open-label, postauthorisation safety surveillance study assessed clinically significant inhibitor development in patients with severe haemophilia A transitioning from moroctocog alfa or other factor VIII (FVIII) replacement products to reformulated moroctocog alfa (AF-CC). Males aged12 years with severe haemophilia A (FVIII:C) < 1 IU/dl), > 150 exposure days (EDs) to recombinant or plasma-derived FVIII products, and no detectable inhibitor at screening were enrolled. Primary end point was the incidence of clinically significant FVIII inhibitor development. Secondary end points included annualised bleeding rate (ABR), less-than-expected therapeutic effect (LETE), and FVIII recovery. Patients were assigned to one of two cohorts based on whether they were transitioning to moroctocog alfa (AF-CC) from moroctocog alfa (cohort 1; n=146) or from another recombinant or plasma-derived FVIII product (cohort 2; n=62). Mean number of EDs on study was 94 (range, 1–139). Six positive FVIII inhibitor results, as determined by local laboratories, were reported in four patients; none were confirmed by a central laboratory, no inhibitor-related clinical manifestations were reported, and all anti-FVIII antibody assays were negative. Median ABRs were 23.4 and 3.4 in patients categorised at baseline as following on-demand and prophylactic regimens, respectively; 86.5 % of bleeding episodes resolved after one infusion. LETE incidence was 0.06 % and 0.19 % in the on-demand and prophylaxis settings, respectively. FVIII recovery remained constant throughout the study. No new safety concerns were identified. This study found no increased risk of clinically significant FVIII inhibitor development in patients transitioning from moroctocog alfa or other FVIII replacement products to moroctocog alfa (AF-CC).
Keywords: Haemophilia A; factor VIII; moroctocog alfa; blood coagulation factor inhibitors; surveillance; safety